2019
DOI: 10.4212/cjhp.v72i1.2863
|View full text |Cite
|
Sign up to set email alerts
|

Drug Shortages in Canada and Selected European Countries: A Cross-Sectional, Institution-Level Comparison

Abstract: <p><strong>ABSTRACT</strong></p><p><strong>Background:</strong> Drug shortages represent a complex global problem affect-ing patients and health care professionals on a daily basis. <br /><strong></strong></p><p><strong>Objectives:</strong> To identify, describe, and compare drug shortages in health care facilities in Canada and 4 European countries in early 2018.<br /><strong></strong></p><p><s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
3
9
0
4
Order By: Relevance
“…Some authorities define the drug shortage from the supply side, and some define it from the demand side. Some authorities define it according to their level in the drug supply chain (whether it's low supply or increased demand), and some define it concerning the timeframe or duration, for example, inability to dispense to a patient in a specific time (Videau et al, 2019a). A study in the EU reported 26 unique definitions 2), and WHO found 56 definitions worldwide.…”
Section: Lack Of Standardized Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authorities define the drug shortage from the supply side, and some define it from the demand side. Some authorities define it according to their level in the drug supply chain (whether it's low supply or increased demand), and some define it concerning the timeframe or duration, for example, inability to dispense to a patient in a specific time (Videau et al, 2019a). A study in the EU reported 26 unique definitions 2), and WHO found 56 definitions worldwide.…”
Section: Lack Of Standardized Definitionmentioning
confidence: 99%
“…In Canada, the Sandoz crisis (2011) started with slow production, ultimately to the plant's shut to meet United States FDA standards. It led to the shortage of morphine (N02AA01) used for patients at the end stage of their lives, and Ondansetron is used to relieve nausea during chemotherapy (Videau et al, 2019a). Cardiovascular drugs like Labetalol (C07A G01) and Metoprolol (C07AB02), Methyldopa (C02AB), and pindolol (C07AA03) are found in the United States FDA drug shortage list (Administration UF, 2020).…”
Section: Drugs Reported In Shortagementioning
confidence: 99%
“…Indépendamment de cette menace, le Canada fait déjà face à de nombreuses pénuries de médicaments au quotidien, en dépit d'une déclaration obligatoire de pénuries réelles ou anticipées imposée aux fabricants canadiens depuis 2017 5 . Plusieurs auteurs ont étudié la problématique des pénuries de médicaments au Canada [6][7][8][9][10][11][12][13] . Ces pénuries sont liées à de nombreuses raisons, dont des pénuries de matière première de médicaments et de fournitures associées à la production de médicaments, des problèmes de fabrication, des enjeux réglementaires liés à la conformité des lieux de production, des modalités de remboursement, etc.…”
Section: Introductionunclassified
“…Ces pénuries sont liées à de nombreuses raisons, dont des pénuries de matière première de médicaments et de fournitures associées à la production de médicaments, des problèmes de fabrication, des enjeux réglementaires liés à la conformité des lieux de production, des modalités de remboursement, etc. 6,7 . Malgré ces efforts législatifs et plusieurs consultations sur le sujet 14 , la situation semble se détériorer.…”
Section: Introductionunclassified
“…Medicines shortages have become a major issue globally [ 1 ], as they affect numerous countries, including Canada [ 2 , 3 ] and European countries [ 4 ] (e.g. Belgium [ 5 , 6 ], Finland [ [7] , [8] , [9] ], France [ 10 , 11 ], Germany [ 12 ], Italy [ 13 , 14 ], the Netherlands [ 15 , 16 ] and Poland [ 17 ]).…”
Section: Introductionmentioning
confidence: 99%